Breast horn; A rare case presentation - Bhirrinta Varughese; Siti Zubaidah Sharif; Ho Kah Yee; Nik Amin Sahid Nik Lah (Elsevier Ltd, 2022)
Breast Cutaneous Horn is a rare case whereby they are basically just nodules composed of keratin projecting above the surface the skin. A 63-year-old lady, para 6 presented with a horn like growth for the past 2 years associated with itchiness. The horn increased in size to about a length of 5 cm associated with on and off itchiness over the horn. No signs and symptoms of malignancy. As comorbidities, patient has hypertension and dyslipidemia which is well controlled on medications. An ultrasound of the breast revealed cutaneous lesion at upper quadrant associated with adjacent skin thickening and no extension into breast parenchyma. A bedside excision was done and the specimen was sent for Histopathology. Histopathology of the lesion revealed Verruca Vulgaris. This case brings to our attention a rare presentation of cutaneous horn over the breast along with its histological findings helping us to distinguish it with other similar cases. Best management would be by excision and to making sure to get a good specimen of the base for dermatopathological evaluation purpose. Cutaneous horns are usually benign lesions. However, there are chances of it being malignant. Therefore, it is best for early intervention such as excision followed by histopathological review for further thorough management.